Museum informatics : people, information, and technology in museums - Marty, Paul F.; Burton Jones, Katherine (New York : Routldege, 2008)
An introduction to museum informatics / Paul F. Marty ##The transformation of the digital museum / Katherine Burton Jones ##Information representation / Paul F. Marty ##Representing museum knowledge / David Bearman ##The information revolution in museums / Darren Peacock ##Information organization and access / Paul F. Marty ##Information policy in museums / Diane M. Zorich ##Metadata and museum information / Murtha Baca, Erin Coburn, and Sally Hubbard ##Interactive technologies / Paul F. Marty ##A world of interactive exhibits / Maria Economou ##Blurring boundaries for museum visitors / Areti Galani, Matthew Chalmers ##Changing needs and expectations / Paul F. Marty ##Understanding the motivations of museum audiences / Kirsten Ellenbogen, John Falk, and Kate Haley Goldman ##Partnerships for progress : electronic access and museum resources in the classroom / Jim Devine ##Collections and consortia / Paul F. Marty ##AMOL ten years on : a legacy of working beyond museum walls / Basil Dewhurst, Kevin Sumption ##Challenges to museum collaboration : the MOAC case study / Richard Rinehart, Layna White ##Information professionals in museums / Paul F. Marty ##Curating collections knowledge : museums on the cyberinfrastructure / Jennifer Trant ##The future of museums in the information age / Maxwell L. Anderson.
boek